The Unethics of Technological Sublimity: The Representation of Environmental Pollution in the Poetry of William Wordsworth - Katsorchi, Stavroula Anastasia (Integrated Journal for Research in Arts and Humanities, 2022)
Within a world that is suffering from an escalating climate crisis, literature and literary theory alike are called to arms. Their mission is to alert both readers and scholars to the looming ecological disaster, but also to encourage the invention and active promotion of ethical ways of dealing with the crisis. Assuming an ecological perspective, this paper turns to the Romantic period and the early signs of industrial destruction and discusses William Wordsworth’s ambiguous, volatile stance towards technology. Building on Edmund Burke and Immanuel Kant, this paper contends that Wordsworth’s early poems represent technology as a sublime object. This portrayal, however, invokes feelings of paralyzing terror, thereby promoting inaction as regards industrialism’s environmental impact. Once technological advancement reaches the Lake District, however, and aesthetic distance is compromised, Wordsworth’s attitude changes, becoming a condemnatory one, moving him to start a campaign against the expansion of the railway. Following Elaine Scarry’s theorization of the link between aesthetics and ethics, it is demonstrated that sublimity constitutes a passive hence unethical way of conceptualizing technology, signalling the need of redefining humankind’s position in and relationship with the rest of the world.